Burden of menstrual symptoms in Japanese women – an analysis of medical care-seeking behavior from a survey-based study - Tanaka E; Momoeda M; Osuga Y; Rossi B; Nomoto K; Hayakawa M; Kokubo K; Wang ECY (Dove Medical Press, 2013)
Erika Tanaka,1 Mikio Momoeda,2 Yutaka Osuga,3 Bruno Rossi,4 Ken Nomoto,5 Masakane Hayakawa,5 Kinya Kokubo,6 Edward CY Wang1 1Health Economics and Outcomes Research, Bayer Yakuhin Ltd, Tokyo, Japan; 2Department of Integrated Women's Health, St Luke's International Hospital, Tokyo, Japan; 3Department of Obstetrics and Gynecology, Faculty of Medicine, The University of Tokyo, Tokyo, Japan; 4Market Access, Bayer Yakuhin Ltd, Osaka, Japan; 5Medical Affairs Women's Health and Dermatology, Bayer Yakuhin Ltd, Osaka, Japan; 6Consumer Goods/Service and Healthcare Industry Consulting Department, Nomura Research Institute, Tokyo, Japan Background: Menstrual symptoms are associated with various health problems in women of reproductive age, and this may impact their quality of life. Despite this, Japanese women are likely to hesitate seeking a specialist's medical help for their menstrual symptoms. Purpose: To study subject parameters including symptom severity, gynecological disorders, and treatments in medical care-seeking women (outpatient) and women opting for self-care (nonvisit), to identify reasons why Japanese women do not see a gynecologist, and to document the benefit of gynecologist visits by assessing the impact on women's daily lives. Methods: Two online surveys were conducted among women aged 15–49 years. Sampling was structured to approximate the age and geographic distribution in Japan. Results of the first survey and part of the second survey on the overall current burden of menstrual symptoms are reported in a separate publication. Further outcomes from the second survey reported in this paper included data from the outpatient (n=274) and nonvisit (n=500) groups on symptom severity, gynecological disorders, medical treatment use, reasons for not seeking medical care, and the improvement of daily life. Results: The outpatient group tended to have greater symptom severity compared to the nonvisit group. Uterine fibroids, dysmenorrhea, endometriosis, and premenstrual syndrome were the most commonly self-reported diagnoses, and oral contraceptives were frequently prescribed at gynecologist visits. Nonvisit group subjects felt that gynecologist consultations were unnecessary or felt resistant to them. Daily life was significantly improved after medical treatment from a gynecologist visit with associated economic savings, whilst the nonvisit group had no change after taking over-the-counter drugs to relieve their menstrual symptoms. Conclusion: The present study results indicate that Japanese women who were suffering from menstrual symptoms could benefit from visiting a gynecologist for easing their symptoms, hence improving their daily life. Keywords: menstrual symptoms, burden, outpatient, care-seeking, MDQ score, patient reported outcome